Correlation Between Serum Uric Acid, Insulin and Hba1c In Type 2 Diabetes Mellitus - Maryam Imtiaz; Samina Saeed; Muhammad Aqeel; Abrar Akbar; Shafaq Saleem; Lubna Meraj (Journal of Rawalpindi Medical College)
Objective: The study aims to determine the relation of serum uric acid levels, glycated haemoglobin A1c (HbA1c) and insulin levels in Type II Diabetes Mellitus as well as their role as potential disease predictors